The Association Between Screen Time and Character Development in Early Childhood at Islamic Educational Institutions - Salsabil Dwi Maharani; Renistiara Medilianasari (Nuris Journal of Education and Islamic Studies, 2026)
Character development is a crucial aspect of the growth and development of young children. Excessive screen time without parental supervision can have negative effects on children’s character development. This study aims to analyze the relationship between screen time duration and character development in young children, specifically in the areas of Islamic based character education that emphasizes the formation of akhlakhul karimah through ta’dib processes in early childhood, specifically in developing honesty, responsibility, empathy, discipline, and respect for others. The study employed a quantitative method with a cross-sectional design. The sample consisted of the entire population of 17 respondents. The research instruments included a screen time questionnaire and a character development questionnaire for children. Data analysis was conducted using univariate analysis to determine the frequency distribution of respondent characteristics and bivariate analysis using the Fisher’s Exact Test with a significance level of p = 0.05 to determine the relationship between screen time and children’s character development. The results showed that 11 children (64.7%) exhibited poor character development, while 6 children (35.3%) exhibited good character development. The results of the Fisher’s Exact Test indicated that the longer a child’s screen time, the greater the likelihood of poor character development. This study highlights the importance of parental guidance in the use of digital media to support character development in early childhood.